Implementing Fire Emergency Response and Health Behaviour Modules to Elevate Islamic Student Knowledge in Boarding Schools - Duhung, Irwan; Ibrahim, Hasbi; Puyu, Darsul S. (Diversity: Disease Preventive of Research Integrity, 2024)
The persistent risks of accidents and occupational diseases in educational settings, including Islamic boarding schools in Indonesia, highlight the need for research on the impact of implementing Health and Safety modules on student knowledge, as evidenced by the high incidence of accidents and inadequate safety measures. The purpose of this study was to analyze the effect of the application of the Fire Emergency Response Modules module on increasing student knowledge. The design of this research is experimental with the form of Pre-Experimental Designs, namely One Group Pretest-Posttest Design. The study took place at Athirah Bukit Baruga boarding school, with a population of junior and high school students. The sample used was purposive sampling with 38 respondents. The results of this study showed a significant effect on increasing student knowledge after being given a fire emergency response module using the Paired Samples T-Test test. Meanwhile, the provision of PHBS module shows that there is a significant effect on increasing safety and health knowledge (p=0.000). The application of the fire emergency response module and PHBS is an effort or mitigation so that students are protected from hazards and diseases in the school environment.